Proposed Model for Ensuring More Security in Cloud by Data Fragmentation Method - Kumar, V. Kiran; Prasad, E.Hari (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is a latest technology where the usage of this service by different clients was increasing rapidly day by day. Cloud provides different services with best facilities to utilize it. Presently many small and large scale businesses were using Cloud services to meet their requirements. The one of the main service in cloud is cloud storage. The major requirements for achieving security in outsourced databases are confidentiality, privacy, integrity, availability. Now a day‘s many companies gives access their clients to store their data in remote storage server i.e. cloud .as well as one of the main issue in cloud is data security. In consideration with the cloud security, in this paper we proposed architecture for storing the data in cloud using the fragmentation method. The detail architecture is discussed in the paper